2022
DOI: 10.5114/pm.2022.119787
|View full text |Cite
|
Sign up to set email alerts
|

Severity of climacteric symptomatology related to depression and sexual function in women from a private clinic

Abstract: Introduction:The climacteric is a natural transition stage in women, in which hormonal changes occur that affect the physical and psychological well-being. Therefore, the objective was to determine the relationship of the severity of climacteric symptomatology with depression and sexual function in women.Materials and methods: It was a descriptive, cross-sectional study, with a sample of 60 women between 40 and 65 years old. The Female Sexual Function Questionnaire-2, the Menopause Rating Scale, and the Beck D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Thus, in the present systematic review study, 14 selected articles were analyzed, in which population samples and variables related to psychological well-being and sexual health were examined. Regarding the former, it was found that 42.9% of the studies used clinical samples as the study population [25][26][27][28][29][30], while 35.7% used representative samples of the general population [31][32][33][34][35]. Only three studies (21.4%) used both types of samples, clinical and general populations [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in the present systematic review study, 14 selected articles were analyzed, in which population samples and variables related to psychological well-being and sexual health were examined. Regarding the former, it was found that 42.9% of the studies used clinical samples as the study population [25][26][27][28][29][30], while 35.7% used representative samples of the general population [31][32][33][34][35]. Only three studies (21.4%) used both types of samples, clinical and general populations [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to sexual health variables, 50% of the studies exclusively evaluated variables linked to sexual functioning, while two articles (14.3%) analyzed aspects other than sexual functioning but in relation to sexual health [28,33]. Five articles (35.7%) examined variables associated with sexual functioning along with other variables related to sexual health [26,27,29,37,38]. For example, Fogh et al [26] reported odds ratios indicating an increasing probability of sexual dysfunction with more/worse depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the present systematic review study, 14 selected articles were analyzed, in which population samples and variables related to mental and sexual health were examined. Regarding the former, it was found that 42.9% of the studies used clinical samples as the study population [25][26][27][28][29][30], while 35.7% used representative samples of the general population [31][32][33][34][35]. Only three studies (21.4%) used both types of samples, clinical and general population [36][37][38].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to sexual health variables, 50% of the studies exclusively evaluated variables linked to sexual functioning, while two articles (14.3%) analyzed aspects other than sexual functioning but related to sexual health [28,33]. 5 articles (35.7%) examined variables associated with sexual functioning along with other variables related to sexual health [26,27,29,37,38].…”
Section: Resultsmentioning
confidence: 99%